ANALISIS SENSITIVITAS di PT AE - Klinton Butar-Butar; Juanita R. Horman (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
PT. AE is engaged in the mining industry which in all its business activities requires a large investment. Therefore, it is necessary to conduct an investment analysis to see how the feasibility of this business using Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate Of Return (IRR) methods. Followed by sensitivity analysis to look at the company's financial condition in case of changes of ±2.50%, ±5.00%, and ±7.50% in revenue and cost of revenue. The results of the calculation of business feasibility analysis obtained a value of 618,450.563, BCR worth 1.698, and IRR worth 35.71%. This indicates that the efforts undertaken are worth carrying out. AE is more sensitive to -5.00% revenue-generating negative NPV, i.e. (121,203.568), BCR at 0.881, and IRR of 2.69%. While the increase of cost of revenue was 7.50%, resulting in a negative NPV of (178,160.513), BCR of 0.830, and IRR of -0.09%.